An analysis of the roles of rural industry in Van Truong commune, Tien Hai district, Thai Binh province - Tuan, Tran Anh (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 2, 2010)
Abstract. The Red River Delta (hereafter as RRD) is one of the two biggest deltas in Vietnam with the population is 19,625 million persons in 2009. It is also the most populous area with the population density of 932 person/km 2 in 2009 (General Statistics Office, 2010). Tien Hai District of Thai Binh Province locates in the eastern part of the RRD, lies in the coastal zone - a sensitive area and affected by the interaction between the mainland and the South China Sea (in Vietnamese as Biển Đông - East Sea). The study area of this research is Van Truong Commune locates in the “ old-land ” area. Analysis of the roles of rural industry will show the characteristics of one of the fundamental features of the rural development process particularly in Tien Hai District as well as in the RRD. Non-farm work is a useful solution to gradually bridge the income gap between urban and rural areas, in which rural industry has been paid attention to develop (UNIDO, 2000). Nevertheless, in a long time, the role of rural industry has been neglected because the mode of production was followed the state-owned enterprises and cooperatives. The objective of the paper is to analyze the realistic situation of rural industry in the RRD by tracing the characteristics of rural industry in Van Truong Commune, Tien Hai District, Thai Binh Province.